Design and implementation of PV emulator based on synchronous buck converter using Arduino Nano microcontroller - Samosir, Ahmad Saudi; Gusmedi, Herri; Huda, Alfin Fitrohul (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This paper discusses the comprehensive design and implementation of a photovoltaic (PV) emulator hardware using a synchronous buck converter. The primary objective is to simulate the electrical characteristics of a real PV module under varying environmental conditions. The process involves detailed simulations carried out using MATLAB/Simulink software to evaluate the performance and accuracy of the emulator model. Various load values were tested to account for the impact of fluctuations in radiation and temperature. The accuracy of the emulator's output characteristics was validated by comparing them with the actual attributes of the SolarWorld Sun-module SW50 PV module. The final step involves constructing the hardware of the PV emulator using electronic components, with an Arduino Nano employed as the controller.